Evaluation of Incisor Index as a Forensic Tool in Gendural Dimorphism – A Study in South Indian Population - S.Prasanna; L.S.Makesh Raj; P.Sai Krishna; V.Jai Santhosh Manikandan; Srikant.N (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Forensic odontology plays a vital role in investigation and presenting the dental evidencesto the court of law. The challenges that are encountered by the forensic odontologist are identifying theindividual which includes certain characteristic features to define an individual. Gendural dimorphismmeans systemic difference in form (shape or size) between individual of different genders in the samespecies. Teeth being considered as one of the stable part which can withstand any environmental changeseven after death of an individual in situations where there are minimal supporting evidences. Odontometricsis the field involving measurements of a tooth.Aim and Objective: This study aims in determining the sex of an individual using incisor index of maxillaryand mandibular arches as a tool in forensic investigation with brief review on literature.Material and Method: A total of 1200 permanent maxillary and mandibular teeth from 150 study modelswith an age range of 18 – 25 yrs were measured using manual divider and scale. The Incisor index (Ii) wasanalysed by using the formula as given by Aitchison (1964). The values were noted separately for maxillaryand mandibular dental arches with regards to central and lateral incisor and these data were subjected forstatistical analysis.Result: Maximum mesio-distal dimension of the all the incisors (maxillary and mandibular) were higher inmales than females. Incisor index of maxilla was higher in female when compared to male which was notstatistically significant. The Incisor index of mandible was higher in male when compared to females whichwas also statistically non-significant.